2007
DOI: 10.1007/bf03326286
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamics of the freshwater-saltwater interface in response to construction activities at a coastal site

Abstract: A numerical model was developed to evaluate the response of groundwater flow and the fresh-saltwater interface in relation to the construction of a particle accelerator at the coastal plain of Tokaimura, Japan. Undisturbed conditions were initially simulated and validated against field observations as a prerequisite for the analysis of predictive scenarios. Groundwater heads and the shape of the saltwater interface were appropriately described by the model, although it tended to underestimate salinity concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…However, this procedure required lot of efforts and cost. The quality of groundwater in coastal aquifers deteriorate as a result of the over pumping of water that was previously discharged in to the sea (Gallardo and Marui, 2007). This problem is common in coastal areas throughout the world and the same has been reported by many researchers (Apello et al, 1987;Gnanasundar and Elango, 1999;Bakker, 2000;Shammas and Jacks, 2007;Chenini and Khemiri, 2009;Praveena and Aris, 2010).…”
Section: Introductionmentioning
confidence: 76%
“…However, this procedure required lot of efforts and cost. The quality of groundwater in coastal aquifers deteriorate as a result of the over pumping of water that was previously discharged in to the sea (Gallardo and Marui, 2007). This problem is common in coastal areas throughout the world and the same has been reported by many researchers (Apello et al, 1987;Gnanasundar and Elango, 1999;Bakker, 2000;Shammas and Jacks, 2007;Chenini and Khemiri, 2009;Praveena and Aris, 2010).…”
Section: Introductionmentioning
confidence: 76%
“…Factor analysis assumes that observed variables are products of linear combinations of some few underlying source variables known as factors. Factor analysis has now been a major tool in the study of groundwater geochemistry as has been demonstrated in several studies (Lawrence and Upchurch, 1983;Briz-Kishore and Murali, 1992;Sabbarao et al 1996;Olobaniyi and Owoyemi, 2006;Aris et al 2007;Gallardo and Marui, 2007;Ramesh Kumar and Riyazuddin, 2008). The present study was set to determine the factors that significantly control the chemistry of groundwater in the phreatic aquifers of Alleppey district.…”
Section: Introductionmentioning
confidence: 94%
“…Basically, the intrusion may be attributed to the over abstraction of groundwater from the aquifer and also from the effect of sea tides (Bear et al, 1999;Abdullah et al, 2002;Gallardo and Marui, 2007). Precipitation of minerals took place during the cation exchange process which was the later effect from the seawater intrusion into the aquifer.…”
Section: Controlling Factors Of Groundwater Hydrochemistry In a Smallmentioning
confidence: 99%